(3GdSjQI GdfHhjIs - (3YHO Gdedc Hf gTGe Hf CjhH GdMejQj GdeYGaQj, CHh eMeO, LeGd GdOjf,J (B213 (3g` s ((3MSf Hf SdjeGf Hf MSjf GdHGQbi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje , ZRhI Hfi Sdje HGdcOQ (B: (3bGd GHf ESMGb adeG bOe QShd Gddg (B( (3U(B) (3GdeOjfI s
(3BNQgG (B:s
(3jG CaVd GdfGS Efi cfJ ai fgQ CUHMJ efg cejd GdeaQO GdUGO bGd GHf gTGe GdHjJ GdChd Yf ZjQ GHf ESMGb Je cJGH s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG JYdjbGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
Keywords: (3GdJGQjNs